Georgia : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report, 2017)
This report evaluates the state of fiscal transparency in Georgia. Georgia has taken important steps to enhance its fiscal transparency practices over the past decade. Fiscal reports have become more comprehensive, with the development of a central government balance sheet and income statement. Fiscal forecasts and budgets have become more forward looking and policy oriented, with the introduction of a four-year medium-term budget framework, formal fiscal objectives, and a program budget classification. In addition, fiscal risk disclosure and analysis have improved dramatically, with the publication of a detailed statement on fiscal risks. At the same time, the evaluation highlights a number of areas where Georgia's fiscal transparency practices could be further improved.